TANGGUNG JAWAB ALGORITMIK PLATFORM DIGITAL ATAS KERUGIAN KONSUMEN: PERBANDINGAN MODEL UNI EROPA DAN INDONESIA - Bisma Putra Pratama; Susanti Sembiring; Tuti Kelana Sembiring (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
AI-driven digital markets transform the legal relationship between platforms and consumers because harm no longer arises only from misleading information, defective products, unfair terms, or contractual breaches, but also from algorithmic systems that shape recommendations, prices, profiling, product visibility, and automated decisions. This article examines digital platform liability for consumer harm through a comparative legal analysis of the European Union and Indonesia. Using normative legal research and a functional comparative method, it shows that the European Union has moved toward a risk-based model through the Artificial Intelligence Act, the Digital Services Act, the General Data Protection Regulation, and the Product Liability Directive. Indonesia, by contrast, still relies on fragmented regimes of consumer protection, electronic systems, electronic commerce, personal data protection, and ethical guidance on artificial intelligence. The article proposes a control-risk-harm nexus to connect platform control, algorithmic risk, and consumer harm. This model allocates responsibility proportionally through algorithmic risk assessment, meaningful transparency, rights to explanation and objection, algorithmic audits, limited reversal of the burden of proof, and effective consumer redress.Keywords: digital platform, consumer harm, artificial intelligence, algorithmic liability, comparative law